EMUAN BELIUNG DI KAWASAN DANAU: Studi Kasus di Kawasan Beberapa Ranu di Jawa Timur - Gunadi Kasnowihardjo (Berkala Arkeologi, 2014)
The stone adze, both rectangular adze or pick adze, is one of the  Neolithic tools’s characteristics. In the Asia-Pacific region, stone adze is contemporaneous with the spreading of Austronesian speakers. In East Java  province two types of stone tools were found in the lakes region, that assumed as a past settlement. Stone adzes found in the lakes region sites are  new data that can complement the data related to the distribution of stone adze in Java, particularly in East Java. Is it true that the findings of the stone adze has a connection with the humans that inhabitants the lake area? Based of these research questions, this research need to be conducted. To answer the research question, spatial archaeological approach issued and also a petrographic analysis of several stone adze samples and stone adze’s rocks material from these research need to be conducted.